AMF-mediated rhizospheric interactions by soil microbiota and metabolites in intercropping of tobacco and maize to regulate the soil nutrients - Liu, Di; Liu, Shulei; Zhao, Peiyan; Nian, Fuzhao; Li, Junying; Han, Ningbo; Yang, Shanqin; Yu, Jialong; Deng, Xiaopeng; Liu, Yating (Frontiers in Plant Science, 2025)
IntroductionColonization of arbuscular mycorrhizal fungi (AMF) can form the root symbiotic network of co-cultured plants roots and hyphae thus promote plant growth. Maize is often intercropped during the harvesting period of tobacco in tobacco-growing areas in China. AMF Colonization has been shown to be an effective approach for regulating the synergistic growth of Nicotiana tabacum and maize.MethodsIn this study, pot experiments were conducted, and samples were analyzed using 16S rDNA and ITS high-throughput sequencing for bacteria and fungi, respectively,and LC-MS/MS widely targeted metabolomics of soil. Differences in microbiota and metabolites in the rhizosphere soil of tobacco and maize, as well as their correlations with the agrochemical properties of soil at the vegetative stage of crop growth, were investigated under AMF colonization to clarify the feedback regulation of plant growth by AMF inoculation and rhizosphere interactions between Nicotiana tabacum and maize.ResultsThe results showed that the growth of tobacco and maize inoculated with AMF was better than that of uninoculated plants, and this was related to the enhancement of plant nutrient uptake by AMF and root interactions between the two crops, which resulted in significant increases in the content of alkaline hydrolyzable nitrogen (N), available phosphorus (P), and available potassium (K) in the rhizosphere soil of tobacco. The stem girth of tobacco and the biomass of maize were significantly higher under intercropping than monoculture, as intercropping increased the relative abundances of Penicillium, Trichoderma, Blastomonas, and Sphingomonas in the rhizosphere soil of tobacco and maize; the abundance of Penicillium was higher in rhizosphere soil of AMF inoculated treatments. AMF inoculation and intercropping cultivation respectively led to the down-regulation of differentially expressed metabolites (DEMs) in the rhizosphere soil of tobacco and maize. Additionally, pH and organic matter are key environmental factors influencing soil microbial communities.DiscussionOverall, intercropping and AMF inoculation mediated rhizospheric interactions by soil microbiota and metabolites in intercropping can regulate plant growth and improving the content of N, P, and K in rhizosphere soil. Our findings provide new insights with implications for AMF application on interactions between the root systems of tobacco with maize or other plants during the tobacco harvesting period.